The Benefit of Bureaucratic Simplification for Bontang City Government - Daryono, Daryono; Ratna Kusuma, Aji; Saropah, Saropah (Journal of Local Government Issues, 2023)
The purpose of this study is to ascertain the advantages of administrative simplification for the Bontang City Government. The methodology in this study is qualitative. Interviews, observation, and documentation were used to gather the data, which was then analyzed utilizing an interactive analytical model through the steps of data reduction, data presentation, and conclusion-making. The research results show benefits bureaucratic simplification in Thus it can be concluded that productivity has increased compared to before the simplification of bureaucracy in the Bontang City Government look of the dimensions of the productivity, responsiveness and accountability.In dimension work productivity among others line of a bureaucratic becoming more efficient and effective. Documents completed immediately according to SOP can be completed immediately on the same day, no need to wait for tomorrow or the day after tomorrow. Bureaucratic simplification in dimension responsiveness benefits include employees become more responsive to work, so that the implementation of services becomes fast and precise. Increase innovation services and the complaints has declined and Complaints about service are decreasing. While benefits bureaucratic simplification in dimension accountability among others more can provide services, motivate employees to employees can develop themselves. Better and well-measured supervision from superiors, tiered supervision.